2004
DOI: 10.1063/1.1782951
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating the gas flow in a numerical model of rf discharges in methane

Abstract: A two-dimensional modified fluid model for a capacitively coupled rf discharge in methane, used for the deposition of diamond-like carbon layers, is presented. The gas velocity calculated with a computational fluid dynamics code is used as an input for the modified fluid model. Convection is taken into account as an additional transport mechanism as well as diffusion and migration. The calculations show that the gas flow results in a shift of the maximum of the densities of the plasma species toward the ground… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…In [28,29] the gas flow was included in the flux equation, in models for ICP discharges in nitrogen. In our group, we have recently developed some models, which incorporate the effect of gas flow, by adding a convection term in the flux equations, for two types of discharges: a dc glow discharge in argon, used as ion source for mass spectrometry [30], and a cc rf discharge in CH 4 , used for plasma-enhanced chemical vapour deposition, to study the effect on the deposition rate and the uniformity of the deposition flux [31]. To our knowledge, there exist, however, no models in the literature that include the gas flow in simulations of hollow cathode discharges.…”
Section: Introductionmentioning
confidence: 99%
“…In [28,29] the gas flow was included in the flux equation, in models for ICP discharges in nitrogen. In our group, we have recently developed some models, which incorporate the effect of gas flow, by adding a convection term in the flux equations, for two types of discharges: a dc glow discharge in argon, used as ion source for mass spectrometry [30], and a cc rf discharge in CH 4 , used for plasma-enhanced chemical vapour deposition, to study the effect on the deposition rate and the uniformity of the deposition flux [31]. To our knowledge, there exist, however, no models in the literature that include the gas flow in simulations of hollow cathode discharges.…”
Section: Introductionmentioning
confidence: 99%
“…Comparing the distributions of N + 2 densities when the flow rate is included and not included, the flow rate not only causes the maximum of the ions density to decrease, and the total ion density in the whole discharge space to decrease, but also causes the ions density to increase near the inlet. A Bogaerts et al have simulated capacitively coupled radio-frequency (ccrf) discharge in methane with a fluid model and have shown that calculated time-averaged CH + 5 ion density decreases with increasing flow rate [9] . The distribution of the mean density of N + ions is similar to that of N + 2 , and the density of N + is about six times less than N + 2 by our calculation, the reason for which can be found in our previous work [12] .…”
Section: The Radial and Axial Electric Fieldmentioning
confidence: 99%
“…Lee et al [7] and Tanaka et al [8] studied the problem of gas flow rate for an ICP discharge in argon and nitrogen. Okhrimovskyy and Bogaerts et al [9] simulated a capacitively coupled radio-frequency (rf) discharge in methane using a twodimension (2D) fluid model including the flow rate in a plasma-enhanced chemical-vapor deposition reactor of H-type geometry. The results explicitly indicate that the flow rate can affect the deposition rate and the uniformity of the deposited layer.…”
Section: Introductionmentioning
confidence: 99%
“…[19]. In addition, the density profile alters when changing the gap between the electrodes due to the competition of the above time scales, [20] or by considering a gas flow module into the fluid model or not, [21] in a capacitively coupled plasma source. Still, the gas flow, together with the feedstock gas fragmentation, multi component mass transport, gas heating, pumping speed, etc., influence the accuracy of gas pressure measurements at the chamber outlet.…”
Section: Introductionmentioning
confidence: 99%